투자자심리지수를 활용한 MBS 조기상환위험의 영향변수에 관한 연구 - 김동환(DongHwan Kim); 박동규(TongKyu Park) (대한부동산학회지, 2017)
본 연구는 한국주택금융공사가 제공하는 2004년 8월부터 2016년 2월까지의 국내 MBS 조기상환율 자료에 근거하여 부동산시장의 투자자심리가 MBS 조기상환율에 미치는 영향을 연구하였다. 부동산투자심리지수는 Baker and Wugler 등에서 활용한 방법론을 활용하여 도출하였으며, 도출된 부동산투자자심리지수가 거시경제상황에 영향을 받을 수 있으므로, Kim and Byun 등에서 선정한 거시경제변수를 활용하여 직교화된 부동산투자자심리지수를 도출하여 분석하였다. 통제변수로는 모기지금리, 실업률, 아파트가격매매지수를 선정하여 벡터자기회귀모형을 통해 실증 분석하였다. 분석결과, 첫째, 모기지 금리는 조기상환율에 음(-)의 영향을 미치는 것으로 나타났으며, 금리스프레드는 조기상환율에 양(+)의 영향을 미치는 것으로 나타났다. 둘째, 아파트가격매매지수는 조기상환율에 양(+)의 영향을 미치는 것으로 나타났다. 셋째, 유의미하지는 않지만 실업률은 조기상환율에 양(+)의 영향을 미치는 것으로 나타났다. 넷째, 부동산 투자자심리는 조기상환율에 음(-)의 영향을 미치는 것으로 나타났다. 본 연구는 부동산투자자심리를 계량화하여 MBS 조기상환율을 설명함으로써, 부동산 시장에서 행동재무학 이론의 활용 가능성과 그 효용에 대하여 유용한 시사점들을 제공할 수 있을 것으로 기대된다. This study is based on the MBS prepayment rate data from August 2004 to February 2016 provided by Korea Housing Finance Corporation. We investigate the relation between the investor sentiment in real estate market and MBS prepayment rate. The real estate investment sentiment index was derived from the methodology used by Baker and Wugler. Since the real estate investor sentiment index may be influenced by the macroeconomic situation, we derive the index by orthogonalizing to the macro economic variables. Mortgage interest rate, unemployment rate, and apartment price index are selected as the control variables and analyzed through the vector autoregressive model. Main results of the study are as follows. First, mortgage interest rate has negative effect on MBS prepayment rate. Second, apartment price trading index has a positive effect on the rate. Third, although not meaningful, the unemployment rate has a positive effect on the rate. Fourth, real estate investor sentiment turns out to show negative effect on MBS prepayment rate. This study quantifies the real estate investor sentiment and explains the MBS prepayment rate based on the sentiment. It will provide some useful implications on the potentials of the behavioral financial models in the real estate market. KCI Citation Count: 2